Comprehensive AIDS prevention programs in prisons: A review study. Issue 4 (1st December 2018) - Zare, Somayeh; Kargar, Mehdi; Ostovarfar, Jeyran; Kaveh, Mohammad Hossein
Abstract : Objective: Since prisoners may acquire AIDS and transmit HIV because of highly risky behaviors, implementation of educational and therapeutic programs is important in decreasing the prevalence of AIDS and transmission of HIV. This study was conducted to recognize different types of interventions and compare their effectiveness regarding prevention of AIDS and its control in prisons. Methods: The ISI, PubMed, Google Scholar, databases were searched with use of "AIDS, " "prison, " "HIV, " and "incarceration" as keywords from January 2000 to March 2017, with access to free full text and English language as limitations. Related articles, including observational, epidemiological, case, and interventional studies, were extracted and those inconsistent with the study's goals were excluded. Results: Forty-three studies were finally selected. The effectiveness of interventions related to AIDS prevention and control in prisons was studied. Conclusion: It seems that theory-based studies conducted with stakeholders participation and evaluated summatively are more successful, because they give a sense of ownership. In addition, considering prison as a setting can lead to more success of these programs.